184. Pharmacist role in antimicrobial stewardship research: a 30-year experience. (31st December 2020) - Pillinger, Kelly E; Jariwala, Ripal; Mercuro, PharmD; Nicholas J; Cwengros, Laura N; Davis, Susan L; Davis, Susan L; Appaneal, Haley
Abstract: Background: Antimicrobial stewardship program (ASP) guidance from the Centers for Disease Control and Prevention recommends co-leadership of both an infectious-diseases (ID) physician and ID-trained pharmacist. Pharmacists play a key role in the therapeutic management, administration, and implementation of ASP interventions. The purpose of this study, conducted on behalf of the Society of Infectious Diseases Pharmacists, was to describe the involvement of pharmacists in publications of ASP interventional research. Methods: A PubMed search was conducted to identify publications in the United States and Canada from 1990–2019 including "antimicrobial (or antibiotic) stewardship" or "antimicrobial (or antibiotic) intervention." Articles were screened for active interventions with comparator arms. A random subset of 100 pharmacist-authored manuscripts were selected using a time-based clustering strategy to review specific study designs, populations, interventions, and endpoints. Results: Of 1, 426 publications, 340 met inclusion. Two-thirds (228/340) of all interventional antimicrobial stewardship studies included a pharmacist author. Pharmacists were lead authors in 59% (135/228) of studies that included a pharmacist. Among the randomized subset of pharmacist-authored manuscripts (n=100), the average impact factor of journals with pharmacists as the first author was 3.52, compared to 5.25 as middle authors. Most studies were inpatient focused (89%), included adults (81%), and conducted in a single-site setting (84%). Pediatrics, immunocompromised, post-acute care, and ambulatory populations comprised less than 10% of the publications. The most common interventions described were audit and feedback (55%), guideline implementation (49%), and education (40%). Endpoints included drug utilization (66%), clinical outcomes (57%), safety events (46%), cost (40%), and appropriateness of therapy (35%). Figure 1. Conclusion: Pharmacists have an integral role in publication and dissemination of ASP research. Opportunities exist in multi-site collaboration as well as research in ambulatory, pediatric, and immunocompromised groups. Future research endpoints should be practical, generalizable, and patient-centered. Disclosures: Kelly E. Pillinger, PharmD, BCIDP, Pharmacy Times (Other Financial or Material Support, Speaker) Haley Appaneal, PharmD, Shionogi (Grant/Research Support)